Znanost, zgodovina, napredek - Pintarič, Miha (Ars et humanitas, 2012)
The function of myth, just like that of science, is achieving a uniform picture of the world in human mind. Myth, however, is based on the supposed truth, not on reality. It is not a beginning, it is the end of any possible discussion. The article, based on French mediaeval and renaissance literature, introduces a view on how Western consciousness wrestled itself out of myth into history.
Keywords: history; zgodovina; napredek; science; znanost; miti; mythology; čas; večnost; krščanstvo; Christianity; francoska književnost; French literature